VLSI Design and Comparative Analysis of Several Types of Fixed and Simple Precision Floating Point Multipliers - Jiménez Pérez, Abimael; Gurrola Navarro, Marco Antonio; Valenzuela De la Cruz, Víctor Manuel; Muñoz Gómez, José Antonio; Aguilar Loreto, Omar (Cultura Científica y Tecnológica, 2021)
Multiplication is an arithmetic operation that has a meaningful impact on the performance of several real-life applications, such as digital signal and image processing. Analysis and comparison of different types of fixed-point multipliers such as Wallace tree, array, and Booth-2 with truncated and non-truncated versions were included in this design. Fixed-point multipliers were used to design floating-point multipliers through a hardware description language. As a result, area and speed values were analyzed. Booth-2 fixed multiplier with truncation and RCA adders present both the longest delay and the largest area consumption. Wallace tree floating-point multiplier required the smallest area and the shortest delay. The 8-bit versions of fixed-point multipliers were physically synthesized, using the Alliance tools, to obtain the layout of the circuits. The integrated circuits were successfully fabricated in a 0.5-μm CMOS technology.